Propidium Monoazide Combined With RT-qPCR Detects Infectivity of Porcine Epidemic Diarrhea Virus - Liang, Gong; Long, Yunzhi; Li, Qianqian; Yang, Liu; Huang, Ying; Yu, Daobing; Song, Wenbo; Zhou, Mingguang; Xu, Gaoyuan; Huang, Chao; Tang, Xibiao (Frontiers in Veterinary Science, 2022)
Presently, RT-qPCR allows sensitive detection of viral particles viruses in epidemic materials, but cannot discriminate non-infectious from infectious viruses. The use of Propidium Monoazide (PMA) coupled with qPCR was assessed to discriminate infectious viruses, while presently there is no established a test method that allows for the detection of infectious Porcine epidemic diarrhea virus (PEDV). Propidium monoazide coupled with qPCR detects infectivity of PEDV. We optimized the method from the selection of primers, the working concentration of PMA and the inactivation method of heat inactivation or UV inactivation.The viruses, which were respectively treated with PMA before qPCR, were inactivated using heat or UV. However, the assay was not able to differentiate between infectious and UV inactivated viruses suggesting that viral capsid damage may be necessary for PMA to enter and bind to the viral genome. The method on naked PEDV RNA suggests that it can be used to detect intact, potentially infectious PEDV and can be used to exclude the detection of free viral RNA by PCR assay.The results indicate an optimal combination of PMA could be very useful for evaluating infectious and noninfectious viruses.